2003
DOI: 10.1074/jbc.m208059200
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Mechanism of Dopamine D1-like Receptor Activation

Abstract: A chimeric D1A dopaminergic receptor harboring the cytoplasmic tail (CT) of the D1B subtype (D1A-CTB) has been used previously to show that CT imparts high dopamine (DA) affinity and constitutive activity to the D1B receptors. However, the D1A-CTB chimera, unlike the D1B subtype, exhibits a significantly lower DA potency for stimulating adenylyl cyclase and a drastically lower maximal binding capacity (Bmax). Here, using a functional complementation of chimeric D1-like receptors, we have identified the human D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…A full-length version of the human dopamine D1 receptor (hD1) with the cytoplasmic tail fused to GFP (hD1-GFP) was subcloned into cDNA3.1 (Invitrogen) and the sequence confirmed by direct sequencing. Plasma membrane localization and functionality of hD1-GFP was validated in transfected human embryonic kidney 293 (HEK293) cells using radioligand binding, whole cell cAMP assays and indirect immunofluorescence microscopy (data not shown) as previously described [42], [43]. In all cases, cRNA was prepared from linearized cDNA templates (mMESSAGE mMACHINE; Ambion, Austin, TX) resuspended in RNAse-free water and stored at −80°C until microinjected.…”
Section: Methodsmentioning
confidence: 99%
“…A full-length version of the human dopamine D1 receptor (hD1) with the cytoplasmic tail fused to GFP (hD1-GFP) was subcloned into cDNA3.1 (Invitrogen) and the sequence confirmed by direct sequencing. Plasma membrane localization and functionality of hD1-GFP was validated in transfected human embryonic kidney 293 (HEK293) cells using radioligand binding, whole cell cAMP assays and indirect immunofluorescence microscopy (data not shown) as previously described [42], [43]. In all cases, cRNA was prepared from linearized cDNA templates (mMESSAGE mMACHINE; Ambion, Austin, TX) resuspended in RNAse-free water and stored at −80°C until microinjected.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are currently no physicochemical data demonstrating this, Tiberi and co-workers (15,(23)(24)(25) have provided evidence consistent with the association of these two receptor domains. By using receptor chimeras and truncation mutants, these investigators have shown that the carboxyl termini of the D 1 -like receptors (D 1 and D 5 ) play critical roles in determining agonist affinity, G protein coupling, and constitutive activity of the receptors (15,(23)(24)(25). Because it is unlikely that these functional effects are directly controlled by the carboxyl termini and it is known that the 3rd cytoplasmic loop is critical for D 1 receptor coupling to G s (26) and also that the 3rd loop of the related D 3 receptor controls receptor affinity for agonists (27), the simplest explanation is the carboxyl terminus influences 3rd loop functions through direct domain-domain interactions.…”
mentioning
confidence: 98%
“…Transfected HEK293 cells were washed with phosphate‐buffered saline (PBS), trypsinized, reseeded in 150‐mm dishes and grown for an additional 48 h. Crude membrane preparations expressing wild‐type or chimeric receptors were prepared as previously described [18]. Membrane preparations were either used immediately (saturation studies) or frozen in liquid nitrogen and stored at −80 °C until needed (competition studies).…”
Section: Methodsmentioning
confidence: 99%
“…Competition studies using DA were done in the presence of 0.1 mM ascorbic acid (dissolved in milli‐Q‐water). Membranes were incubated for 90 min at room temperature and binding assays stopped using rapid filtration through glass fiber filters (GF/C, Whatman) as described before [18]. Radioactivity bound to filters was measured using liquid scintillation counting (Beckman Counter, LS 6500).…”
Section: Methodsmentioning
confidence: 99%